Reclassification of good-risk seminoma: prognostic factors, novel biomarkers and implications for clinical management. (18th March 2019) - Casadei, Chiara; Schepisi, Giuseppe; Menna, Cecilia; Chovanec, Michal; Gurioli, Giorgia; Gallà, Valentina; Altavilla, Amelia; Marcellini, Massimo; Bellia, Salvatore Roberto; Lolli, Cristian; Mego, Michal; Rosti, Giovanni; et al.
Germ cell tumors represent 11% of the cancers diagnosed in adolescent males and are the most common solid tumors in adult men between the ages of 20 and 35. Pure seminoma accounts for around 50% of all testicular germ cell tumors. The prognostic classification of the International Germ Cell Cancer Collaborative Group for good-prognosis seminoma includes both nodal disease and pulmonary visceral metastases. In this article, we analyzed recent data on prognosis and outcome of good-prognosis seminoma to revise the traditional classification of the disease and improve tailored treatment.